Preparation of hollow SiC spheres by combustion synthesis. Issue 8 (14th April 2022) - Wang, Liyuan; He, Gang; Sun, Shaolin; Fang, Shijie; Li, Zhipeng; Yang, Zengchao; Li, Jiangtao
Abstract: Hollow spherical β‐SiC was successfully prepared in argon by combustion synthesis using Si powder and polytetrafluoroethylene (PTFE) powder. The phase composition and morphology of spherical products can be controlled by adjusting the Si/C2 F4 molar ratio ( M Si/(C2F4) ). When M Si/(C2F4) = 3, the phase content of β‐SiC is the highest (up to 85.54%), and hollow spherical products obtained; When M Si/(C2F4) ≥ 5, the Si/SiC microspheres are solid. The synthesis mechanism of hollow β‐SiC microspheres is as follows: Si particles react with PTFE releasing heat. Then unreacted Si absorbs heat to form liquid phase microspheres, which is equivalent to the core template to form β‐SiC microspheres by reaction with cracked C. Meanwhile, the silicon diffuses from the core to the shell to form the cavity. This method can synthesize the hollow spherical β‐SiC in a simple way without prearranged spherical template and long synthesis cycle.